Cinderella [videorecording (Blu-Ray + DVD)] - Weitz, Chris, 1969-; James, Lily, 1989-; Blanchett, Cate, 1969-; Madden, Richard, 1986-; Bonham Carter, Helena, 1966-; Skarsgård, Stellan; Grainger, Holliday, 1988-; McShera, Sophie; Anozie, Nonso, 1979-; Jacobi, Derek ([Walt Disney Studios Home Entertainment], 2015)
Celebrate the transformative power of kindness with Disney's Cinderella, a modern classic that shines with beauty, imagination ... and magic! Despite being bullied by her stepmother and stepsisters, a spirited Ella refuses to despair or retaliate, choosing instead to honor her mother's last words: "Have courage and be kind". Then one day, she meets a remarkable, like-minded man in the woods and she resolves to take charge of her fate in hopes of seeing him again. Add a royal ball, a Fairy Godmother, and an enchanted glass slipper and suddenly-magic becomes reality! Cinderella will captivate your whole family forever after.